2019
DOI: 10.1177/2041669519841071
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Ordinal Position Effect: Stability Across Sense Modalities and the Hands Crossed Context

Abstract: The ordinal position effect posits that items positioned earlier in an ordinal sequence are responded to faster with the left key than the right key, and items positioned later in an ordinal sequence are responded to faster with the right key than the left key. Although the mechanism of the ordinal position effect has been investigated in many studies, it is unclear whether the ordinal position effect can extend to the auditory modality and the hands crossed context. Therefore, the present study employed days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…We believe, however, that these findings relate to a mechanism that is qualitatively different from serial order WM, which we investigated here with the OPE. Our main argument is that the OPE is based on an allocentric coding of space, 6,26,27 whereas spatial competence in terms of allocentric codes only emerges around 22 months of age 28 . Moreover, in the previous work, we have framed the OPE in terms (hippocampal dependent) of item–space binding (i.e., coding serial order across items by binding the items to systematically arranged, spatially defined position markers 15,16 ), a mechanism recycled from the brain's systems for mnemonic coding of external space.…”
Section: Discussionmentioning
confidence: 95%
“…We believe, however, that these findings relate to a mechanism that is qualitatively different from serial order WM, which we investigated here with the OPE. Our main argument is that the OPE is based on an allocentric coding of space, 6,26,27 whereas spatial competence in terms of allocentric codes only emerges around 22 months of age 28 . Moreover, in the previous work, we have framed the OPE in terms (hippocampal dependent) of item–space binding (i.e., coding serial order across items by binding the items to systematically arranged, spatially defined position markers 15,16 ), a mechanism recycled from the brain's systems for mnemonic coding of external space.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies identified the ordinal position effect in the processing of multiple types of ordinal symbols, such as letters, days, months, overlearned sequences and temporary ordinal sequences (Gevers et al, 2003(Gevers et al, , 2004Previtali et al, 2010;van Dijck & Fias, 2011;Wang et al, 2019). These studies indicated that the occurrence of the ordinal position effect suggests that ordinal symbols, similar to numbers, are represented spatially from left to right according to their original ordinal sequence and depending on one's reading and writing habits.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, the results also suggested that the ordinal position effect could not be influenced by the spatial locations of the ordinal symbols in the ordinal position classification task. Previous studies indicated that the ordinal position effect occurred during the processing of ordinal symbols acquired by overlearning (e.g., letters) and those induced by successively presented stimuli (e.g., numbers) when participants were asked to judge the ordinal positions of probe stimuli (Fischer et al, 2010;Gevers et al, 2003;Ginsburg et al, 2017;Ginsburg & Gevers, 2015;Huber et al, 2016;Treccani & Umiltà, 2011;van Dijck & Fias, 2011;Wang et al, 2019). Therefore, these studies consistently indicated that the occurrence of the ordinal position effect implied that ordinal symbols, similar to numbers, were represented spatially from left to right according to their original ordinal sequence and consistent with one's reading and writing habits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that a number contains spatial properties and is represented spatially based on its numerical magnitude from left to right (Aiken & Williams, 1973;Galton, 1880;Restle, 1970), Dehaene et al interpreted this SNARC effect as the result of the mental spatial representation of numbers. Therefore, the SNARC effect is regarded as the gold standard to examine whether a specific symbol is represented spatially in one's mind, and it has been widely applied in other studies (Shi et al, 2019;Wang et al, 2019;Zhang et al, 2019).…”
mentioning
confidence: 99%